Vitamin D Status and Multiple Sclerosis Relapse - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
Researchers at University of California, San Francisco, and State University of New York at Stony Brook, NY consecutively recruited patients with pediatric-onset multiple sclerosis into a prospective cohort to determine if vitamin D status is associated with the rate of subsequent clinical relapses.